2018
DOI: 10.1016/j.bja.2017.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, characteristics, and predictive factors for medication errors in paediatric anaesthesia: a prospective incident monitoring study

Abstract: Medication errors are not uncommon in paediatric anaesthesia. Identification of the mechanisms related to medication errors might allow preventive measures that can be assessed in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 37 publications
2
63
0
1
Order By: Relevance
“…Consistent with previous literature, multiple studies included in this review reported increased rate of medication error, critical incident, and/or cardiac arrest in patients <1 year of age . Several included studies found no association between age and risk of medication error or critical incident rate . Of note, the studies that did not find an association between age and risk had among the smallest sample sizes of those included in this review.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Consistent with previous literature, multiple studies included in this review reported increased rate of medication error, critical incident, and/or cardiac arrest in patients <1 year of age . Several included studies found no association between age and risk of medication error or critical incident rate . Of note, the studies that did not find an association between age and risk had among the smallest sample sizes of those included in this review.…”
Section: Discussionsupporting
confidence: 77%
“…It is noteworthy that there is considerable heterogeneity with regard to the country in which the study took place, including European, North American, African, and Asian nations. Time period of patient observation is also an important source of heterogeneity among included studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations